Studies in the Corallinaceae with special reference to Fosliella and Pneophyllum in the British Isles - Chamberlain, Y. M. (London British Museum Natural History, 1983)
Bulletin of the British Museum : Botany series 11(4) 29 Dec 1983
Keywords: Pneophyllum; Fosliella; Corallinaceae